UPAYA PENINGKATAN KEBERSIHAN GIGI DAN MULUT MELALUI UPAYA PROMOTIF DAN PREVENTIF PENYAKIT GIGI DAN MULUT DI SD N 1 CELUK - I Made Budi Artawa (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2020)
Abstract           The results of the identification of problems with 112 State elementary school students 1 Celuk average knowledge of maintenance of dental and mouth health criteria failed, oral hygiene criteria were moderate, brushing skills were incorrect criteria.  So that the problem "Is the promotion and prevention of oral and dental health can improve oral and dental hygiene in students of SD N 1 Celuk Sukawati Gianyar in 2019. The aim is to improve dental and oral hygiene in elementary school students N Celuk Sukawati Gianyar in 2019.          Community service activities were carried out at SD N 1 Celuk Sukawati Gianyar. Timing of the Pre-test, dental and oral hygiene check, joint toothbrushes were carried out on September 20, 2019. Dental and oral health services were carried out on September 23, 2019. The post-test was carried out on October 4, 2019. The target was 112 students, parties involved in the service team, laboratory staff, principals and teachers, and students.           The most knowledge pre-test results failed criteria 91 people (80.36%), none of the students had very good knowledge, the average value of 33.13. The majority of post-test (35.71%) people have very good knowledge of the criteria. Dental and oral hygiene had the most criteria being 98 (87.50%), and the least good criteria were six people (5.36%). The average OHI-S is 2.14. The post-test results were at most 104 good criteria (92.86%) and none had bad criteria. Average value of 0.14. Tooth brushing skills All students have the wrong brushing teeth criteria. The results of post-test brushing skills especially brushing teeth lingual.            Conclusion, promotive and preventive efforts can improve dental and mouth hygiene of students at SD N 1 Celuk, Sukawati Subdistrict, Gianyar Regency in 2019. It is recommended that community health centers officials in SD N 1 Celuk area provide regular and continuous promotive and preventive services. Keywords: PKM, Elementary Students, Promotive, Preventive